Efektifitas Penegakan Hukum Tindak Pidana Cyber Gambling Endorsement Di Indonesia - Bintang Artsena Jendraningrat (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
Cyber crime or criminal action in the internet network is not a new thing in Indonesia, one of which is Cyber Gambling Endorsement. One of the factors is the rise in criminal acts due to the existence of endorsement activities which are very prevalent on social media or on certain sites on the internet. And this is certainly included in the qualifications or elements of online gambling crime and contained with Article 45 paragraph (2) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning about Electronic Information and Transactions, where this Endorsement activity refers to the distribution or transmitting the gambling-laden site it self, so that it can be freely accessed by many people in individual or groups in Indonesia. In this study the authors used an empirical research method with data collection which was then used to answer the problem formulation, namely official documents, legislation, literature or official books, interviews, and also taking online questionnaires. The data analysis used is descriptive analytical, the analysis used is a qualitative approach to primary data and secondary data. The purpose of this study is to analyze the factors that cause the occurrence of many crimes of Cyber Gambling Endorsement in Indonesia and also what are the efforts of law enforcers in dealing with criminal acts of Cyber Gambling Endorsement in Indonesia and what obstacles are then faced by law enforcers in Indonesia.